PERAN PENDIDIKAN AGAMA ISLAM DALAM MENGATASI KRISIS MORAL DI ERA DIGITAL: KAJIAN LITERATUR INTEGRATIF PADA ANAK USIA SEKOLAH DASAR - Edo Ferdian; Itsna Rusydiana; Ganda Yulida Trisakti Pamungkas (Al-ATHFAL: Jurnal Pendidikan Anak, 2026)
The development of digital technology, the rapid flow of information, and widespread virtual interactions have presented new challenges for the moral formation of teenagers. The moral crisis does not only appear in the form of conventional social delinquency, but also develops in the digital space through hate speech, cyberbullying, the spread of hoaxes, weak communication etiquette, low empathy, and lack of responsibility in the media. This article aims to analyze the role of Islamic Religious Education in overcoming the moral crisis of teenagers in the digital era. This research uses a qualitative approach with a type of library research and an integrative literature review design. Data was obtained from scientific journal articles for 2020–2026, theoretical books, proceedings, and relevant education policy documents. Data analysis was carried out using thematic analysis through the stages of identification, filtering, coding, organizing themes, and synthesis of findings. The results of the study show that Islamic Religious Education has a preventive, educative and transformative role in developing adolescent morals. Preventively, PAI builds a stronghold of values, self-control and religious awareness. Educationally, PAI teaches moral values, manners, social responsibility and digital ethics contextually. Transformatively, PAI forms a religious character so that Islamic values ​​are realized in real behavior, both in social and digital spaces. This study confirms that PAI learning needs to be developed in a reflective, participatory, example-based manner and integrated with religious digital literacy.